Role of Anxiety in the Pathophysiology of Irritable Bowel Syndrome: Importance of the Amygdala - Myers, Brent; Greenwood-VanMeerveld, Beverley (Frontiers in Neuroscience, 2009)
A common characteristic of irritable bowel syndrome (IBS) is that symptoms, including abdominal pain and abnormal bowel habits, are often triggered or exacerbated during periods of stress and anxiety. However, the impact of anxiety and affective disorders on the gastrointestinal (GI) tract is poorly understood and may in part explain the lack of effective therapeutic approaches to treat IBS. The amygdala is an important structure for regulating anxiety with the central nucleus of the amygdala (CeA) facilitating the activation of the hypothalamic-pituitary-adrenal (HPA) axis and the autonomic nervous system in response to stress. Moreover, chronic stress enhances function of the amygdala and promotes neural plasticity throughout the amygdaloid complex. This review outlines the latest findings obtained from human studies and animal models related to the role of the emotional brain in the regulation of enteric function, specifically how increasing the gain of the amygdala to induce anxiety-like behavior using corticosterone (CORT) or chronic stress increases responsiveness to both visceral and somatic stimuli in rodents. A focus of the review is the relative importance of mineralocorticoid receptor (MR) and glucocorticoid receptor (GR)-mediated mechanisms within the amygdala in the regulation of anxiety and nociceptive behaviors that are characteristic features of IBS. This review also discusses several outstanding questions important for future research on the role of the amygdala in the generation of abnormal GI function that may lead to potential targets for new therapies to treat functional bowel disorders such as IBS.